"Please Don't Take This": Rural Gentrification, Symbolic Capital, and Housing Insecurity. (30th August 2021) - Sherman, Jennifer
Abstract: Based on 84 in-depth interviews and ten months of ethnographic fieldwork, this paper examines the impacts of gentrification and housing shortages in a rural Western U.S. community. In-migration by wealthy outsiders to the high-amenity community has driven up housing costs, privileging newcomers over longtime locals. The paper examines the impacts of social inequality on the community's most vulnerable residents, exploring the ways in which housing insecurity is reproduced and how formal and informal infrastructures fail to provide adequate housing options for low-income residents. While income is a significant factor in determining an individual or family's ability to access stable and affordable housing, symbolic resources, including social and moral capital are also found to play significant roles. The paper describes the mechanisms by which these resources come into play, illustrating how a lack of financial, social, and moral capital disadvantages residents in their struggles to procure housing. It finds that in a rural context where in-migration leads to high inequality, socially marginalized rural residents face a distinctive set of challenges and disadvantages that magnify housing instability and deepen exclusion and precariousness.